Antimicrobial resistance genes in weaned pigs: quantitative abundance and group dynamics assessed by qPCR - Jaleta, Megarsa; Junker, Vera; Hölzel, Christina; Zentek, Jürgen; Amon, Thomas; Nübel, Ulrich; Kabelitz, Tina (Frontiers in Veterinary Science, 2026)
Antibiotic resistance genes (ARGs) linked with the selection of resistant bacteria in intensive commercial livestock production require regular surveillance. This study quantified ARG abundances in weaner pigs, with emphasis on inter-individual variation and temporal trends of ARG dynamics over 8 weeks in a flat-deck housing system. Fecal samples from 103 individual pigs and 53 pooled pen-floor collections were analyzed. Broad-spectrum ARG profiling of pooled DNA from both sample types was performed using high-throughput qPCR (SmartChip), while standard qPCR quantified eight ARGs (aadA1, blaTEM, dfrA12, erm(B), lnu(F), qnrS, sul2, and tet(A)) and the 16S rRNA gene in all samples. Among the quantified ARGs, erm(B) and aadA1 were the most abundant, while qnrS was least frequently detected. Substantial inter-individual variation was observed for most ARGs, despite pigs living together under the same management conditions. Pooled pen-floor feces exhibited significantly higher ARG loads than individual fecal samples, suggesting that resistome profiles at the pen-floor level cannot be accurately inferred from fresh feces of individual animals. Temporal analysis revealed that 16S rRNA gene copies increased during the later period, while tet(A) and sul2 decreased, suggesting age-related effects. These findings reveal pronounced intra-cohort variability in ARG abundance among weaner pigs and underscore the impact of weaning-associated factors on resistome composition. Future investigations should examine the contribution of gut microbiome dynamics and evaluate dietary interventions aimed at stabilizing ARG profiles and mitigating the resistance development of microbial resistance.